IMPLEMENTASI PENCATATAN DAN PEMELIHARAAN BARANG MILIK DAERAH (BMD) MELALUI KIB DIGITAL DI PEMERINTAH PROVINSI JAWA BARAT - Athaya Farhah Pradita; Neneng Yani Yuningsih; Tiyan Rahmanul Hakim (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study is motivated by persistent challenges in the recording and maintenance of Regional Assets (Barang Milik Daerah/BMD), despite the implementation of the Digital Inventory Card (KIB Digital) system in the Government of West Java Province. The study aims to analyze the implementation of BMD recording and maintenance through KIB Digital, identify inhibiting factors, and examine government efforts to optimize its application. The main argument of this research is that the digitalization of asset management through KIB Digital can enhance accuracy, transparency, and accountability when supported by adequate human resources and effective governance. This research employs a qualitative descriptive method. Data were collected through observation, in-depth interviews, documentation, and literature review, with purposive sampling involving asset managers, assistant asset officers, and relevant officials within the General Bureau of the Regional Secretariat of West Java Province. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, supported by source triangulation. The findings indicate that the implementation of KIB Digital has improved administrative order and transparency in regional asset management; however, challenges remain, including limited human resources, uneven understanding of the digital system among staff, and coordination between work units that has not yet been systematically integrated. Therefore, strengthening human resource capacity, enhancing training and socialization, and improving coordination mechanisms are necessary to optimize the implementation of KIB Digital. Keywords: Digital Inventory Card, Regional Assets, Policy Implementation, Local Government, Asset Digitalization.